The meaning of modern business : - Eells, Richard (Columbia Unvi. Press, 1960)
This book has been written as an introduction to the philosophy of a great institution - the modern business corporation. Such a philosophy, when finally matured, will make the corporation more comprehensible and provide norms for corporate performance in a society that relies so heavily upon this remarkable organizational instrument.